Efficacy and safety of modified fluorouracil/leucovorin plus irinotecan and oxaliplatin (mFOLFIRINOX) compared with S‐1 as second‐line chemotherapy in metastatic pancreatic cancer. Issue 6 (10th May 2021) - Ikezawa, Kenji; Kiyota, Ryosuke; Takada, Ryoji; Daiku, Kazuma; Maeda, Shingo; Imai, Toshihiro; Abe, Yutaro; Kai, Yugo; Yamai, Takuo; Fukutake, Nobuyasu; Nakabori, Tasuku; Ashida, Reiko; et al.
Abstract: Background and Aim: The optimal standard second‐line chemotherapy for metastatic pancreatic cancer (MPC) remains unclear. Here, we evaluated the efficacy and safety of modified fluorouracil/leucovorin plus irinotecan and oxaliplatin (mFOLFIRINOX) compared with oral fluoropyrimidine S‐1 as a second‐line chemotherapy in patients with MPC. Methods: We retrospectively reviewed 76 consecutive patients with metastatic pancreatic adenocarcinoma who underwent mFOLFIRINOX or S‐1 treatment as a second‐line chemotherapy after gemcitabine plus nab‐paclitaxel (GnP) failure at our department between December 2014 and February 2019. Results: Patients who underwent mFOLFIRINOX treatment exhibited significantly better objective response rates (ORRs) and progression‐free survival (PFS) than S‐1 (ORR, 20.0% vs 0%, P  = 0.003; PFS, 3.7 vs 2.1 months, P  = 0.010). Although baseline patient characteristics of age, performance status, and serum albumin levels differed significantly between the two groups, mFOLFIRINOX was identified as an independent factor of favorable PFS on multivariate analyses. Grade 3–4 neutropenia and peripheral sensory neuropathy occurred more frequently in the mFOLFIRINOX group. The median overall survival from the initiation of second‐line chemotherapy was not significantly longer in the mFOLFIRINOX group than in the S1 group (8.5 vs 5.8 months, respectively; P  = 0.213); however, the 8‐month survival rate was significantly higher in the mFOLFIRINOX group (56.0% vs 27.5%, respectively; P  = 0.030). Conclusions: mFOLFIRINOX as a second‐line regimen contributed to favorable treatment outcomes, but induced more frequent adverse events than S‐1. On multivariate analyses, mFOLFIRINOX was identified as an independent factor with favorable PFS, suggesting that mFOLFIRINOX could be a promising treatment option for patients with GnP failure. Abstract : The optimal standard second‐line chemotherapy for metastatic pancreatic cancer (MPC) remains unclear. In this retrospective study for MPC patients with gemcitabine plus nab‐paclitaxel (GnP) failure, modified fluorouracil/leucovorin plus irinotecan and oxaliplatin (mFOLFIRINOX) as a second‐line regimen contributed to favorable treatment outcomes but induced more frequent adverse events than S‐1. On multivariate analyses, mFOLFIRINOX was identified as an independent factor with favorable progression‐free survival, suggesting that mFOLFIRINOX could be a promising treatment option for patients with GnP failure.